English Competency Test (UK BIG) in ILC Anugerah: Between Hope And Fact - I Made Ardana Putra; Ni Ketut Suciani; Anak Agung Raka Sitawati (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The English Competency Test (UK BIG) has been undertaken by English Competency Certification Board (LSK) since 2009. It has authority to conduct the English Competency Test which preceded by coordinating with Directorate of Course and Training Development, Early Childhood Education Non Formal and Informal, Ministry of Education and Culture of Republic of Indonesia (Direktorat Pembinaan Kursus dan Pelatihan PAUDNI, Kemendikbud RI). In the stage of English Competency Test (UK BIG), English Competency Certification Board (LSK) has full authority as the organizer which realization is entirely handed to the English Competency Test Centre (TUK BIG) which has spread over Indonesia. TUK BIG acts as the organizing institutionAs we have known that English Competency Test (UK BIG) is projected to replace the position of National exam but unfortunately it is not broadly known by education community and public society. Besides, the supports and motivations from Ministry of Education and Culture is very strongly, the spirit of LSK BIG is also very highly and  TUK BIG have been formed nearly at every capital city in Indonesia. However, the echo of UK BIG is not clearly seen yet, even some efforts had been done thoroughly. Concerning to this reality, this writing will make segments about recent UK BIG: Between hope and fact.